2018
DOI: 10.1371/journal.pone.0196383
|View full text |Cite
|
Sign up to set email alerts
|

The biomechanical role of overall-shape transformation in a primitive multicellular organism: A case study of dimorphism in the filamentous cyanobacterium Arthrospira platensis

Abstract: Morphological transformations in primitive organisms have long been observed; however, its biomechanical roles are largely unexplored. In this study, we investigate the structural advantages of dimorphism in Arthrospira platensis, a filamentous multicellular cyanobacterium. We report that helical trichomes, the default shape, have a higher persistence length (Lp), indicating a higher resistance to bending or a large value of flexural rigidity (kf), the product of the local cell stiffness (E) and the moment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…When, in a culture of a helically coiled strain, a few filaments happen to become straight, they tend to become predominant [ 38 , 39 ]. Environmental factors, mainly temperature, physical and chemical conditions, may affect the trichome geometry, and several studies consider straight trichomes to be a symptomatic feature of crops grown under stressful conditions, which are associated with slowed metabolism [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…When, in a culture of a helically coiled strain, a few filaments happen to become straight, they tend to become predominant [ 38 , 39 ]. Environmental factors, mainly temperature, physical and chemical conditions, may affect the trichome geometry, and several studies consider straight trichomes to be a symptomatic feature of crops grown under stressful conditions, which are associated with slowed metabolism [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two crude extracts of phycocyanins (PC) were prepared at the Institute of Agricultural Technology, Suranaree University of Technology. Herein, the crude extracts PC were prepared from Arthrospira platensis stain C005H (wild-type spirulina, helical trichomes) and Arthrospira platensis stain C005L (straight trichomes) by ultrasonic -assisted extraction method (Chaiyasitdhi et al, 2018). C005H strain was generously provided by Applied Algal Research Laboratory, Faculty of Science, Chiang Mai University.…”
Section: Methodsmentioning
confidence: 99%
“…Enomoto et al (2020) reported for Arthrospira that the formation of clumps, that assume the shape of the containing vessel (Ohmori et al 1998), is stimulated by cyclic adenosine monophosphate (cAMP), which is correlated to an increase of respiration and trichome motility; cAMP signaling is also probably regulated by light (Ohmori and Okamoto 2004). In addition, straight trichomes seem to improve directionality and speed of gliding motility (Chaiyasitdhi et al 2018). Ohmori et al (1992) suggested that cAMP might stimulate extracellular polysaccharide production, which is directly involved in cell aggregation.…”
Section: Regimementioning
confidence: 99%